Erythropoietin Potentiates Thrombus Development in a Canine Arterio-Venous Shunt Model - Wolf, Roman F; Gilmore, Laura S; Friese, Paul; Downs, Tamyra; Burstein, Samuel A; Dale, George L (Thrombosis and Haemostasis, 1997)
Erythropoietin (EPO) has been previously shown to affect platelet as well as red cell production. In addition, recent studies demonstrated that platelets from EPO-treated dogs are hyperreactive towards thrombin when compared to age-matched, control platelets. This report extends these observations by quantitating the thrombogenic potential of EPO in dogs. Dogs with arterio-venous (A-V) shunts received 100 U EPO/kg/day for 6 days, and thrombogenicity was serially monitored by insertion of a thrombotic surface into the A-V shunt. The resulting experimental thrombi were analyzed for platelet and erythrocyte content after formalin-fixation and chymotrypsin digestion, a technique which allows non-isotopic quantitation of cellular components. By day 5 of EPO-administration all animals demonstrated a significant increase in platelet and red cell content of the experimental thrombi; the average increase in platelet number was 2.94 ±0.12 fold (mean ± 1 SE; n = 3; p = 0.006) above baseline while that for red cells was 2.46 ±0.18 fold above baseline (p = 0.023). After cessation of EPO, thrombogenicity returned to normal. During EPO-treatment, the percentage of thiazole orange-positive (TO+) platelets increased significantly to 17.2 ± 1.6% (mean ± 1 SE; n = 3) on day 5 compared to a pre-treatment level of 8.5 ± 0.9% (p = 0.029). Although the percentage of TO+ erythrocytes also increased during the short course of EPO administration, the change was not significant. Despite the increases in TO+ cells, total platelet and erythrocyte counts did not change significantly within the time frame of these experiments. Fibrin/fibrinogen content of the experimental thrombi was unaltered with EPO-treatment. These data demonstrate that human EPO is pro-thrombotic in dogs and, in conjunction with earlier studies, suggest that hyperreactive platelets may be responsible for the potentiated thrombogenicity.